Christic witnessing: a practical response to ecological trauma - Middleton, TA (Taylor and Francis, 2022)
Suffering in the ecological realm exhibits structural parallels with diagnoses of human trauma. Viewing ecological suffering as traumatic allows for recent work in trauma theology to be applied in an ecological context. This article focusses specifically on the breakdown of communication that characterises traumatic events. In the ecological case, this is often a human failure to attend to suffering in the rest of the ecosphere. What is required is a witness to this ecological trauma. Following Shelly Rambo, such witnessing is not about proclamation or imitation, but rather entails simply remaining with the suffering. For Christians, Christ can be one such witness. In his life and his death, he bears witness to the traumas of the earth—especially in his refusal to abandon our wounded world at the crucifixion. And this Christic witnessing provides a blueprint for our own, practical response: not imitating the self-sacrifice, but following the witness. One, tangible example of this is given by the Stations of the Forests resource. Here, the fourteen stations of the cross are recast as a witness to the traumas of contemporary deforestation. Resources like this illustrate how a model of Christic witnessing can constitute a practical response to ecological trauma.